1999
DOI: 10.1111/j.1574-695x.1999.tb01342.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of immunisation against diphtheria, pertussis and tetanus (DPT) in relation to sudden infant death syndrome

Abstract: Epidemiological evidence indicates infants immunised against diphtheria, pertussis and tetanus (DPT) are at decreased risk of sudden infant death syndrome (SIDS). Asymptomatic whooping cough and pyrogenic toxins of Staphylococcus aureus have been implicated in the aetiology of SIDS. The objectives of the present study were: (1) to determine if the DPT vaccine induced antibodies cross-reactive with the staphylococcal toxins; (2) to determine if antibodies to the pertussis toxin (PT) and the staphylococcal toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

1999
1999
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…These toxins have been identified among SIDS infants in Britain, France and Australia. In our local population there was a decline in antibodies to TSST and SEC 1 during late pregnancy but not SEA or SEB [53]. Methods to reduce colonisation by S. aureus or methods to boost passive or active immunity to these toxins during the early months of life might further reduce the numbers of SIDS deaths.…”
Section: Discussionmentioning
confidence: 79%
“…These toxins have been identified among SIDS infants in Britain, France and Australia. In our local population there was a decline in antibodies to TSST and SEC 1 during late pregnancy but not SEA or SEB [53]. Methods to reduce colonisation by S. aureus or methods to boost passive or active immunity to these toxins during the early months of life might further reduce the numbers of SIDS deaths.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have shown that vaccines are not associated with an increased risk of SIDS [8,24]. Some studies have even shown a reduced risk of SIDS associated with vaccinations [5]. Despite this, from time to time this controversy is reopened [3].…”
Section: Discussionmentioning
confidence: 99%
“…As with inflammatory responses to sepsis, cytokines, induced by bacterial toxins, might cause physiological changes leading to death [20,21]. In support of this hypothesis, Essery et al observed that anti-DPT immunization induces antibodies that cross-react with pyrogenic staphylococcal toxins, which have been implicated in several cases of SD [22]. Hence, these authors suggested that part of the protective effect of DPT vaccination in relation to SD may be due to the induction of cross-reacting antibodies that are capable of reducing the effects induced by the pyrogenic staphylococcal toxins.…”
mentioning
confidence: 88%